Implementation Of The National Health Insurance Policy Within The Banggai District Health Office - Djohanis, Herni; Hardiyanto, Hardiyanto; Lestari, Sri; Supadiyasa, I Wayan (Public Policy Journal, 2025)
The National Health Insurance Program (Jaminan Kesehatan Nasional,JKN) in Banggai Regency shows several problems in its implementation process.These issues include an insufficient number of health workers as well asinadequate facilities and infrastructure in direct health service units, which resultin suboptimal services for JKN participants. Considering these existingphenomena, the author conducted this research to analyze the implementationof the National Health Insurance Program policy in Banggai Regency. Theresearch sites included the Banggai Regency Health Office, Luwuk Regional PublicHospital (RSUD Luwuk), and selected community health centers (Puskesmas) inBanggai Regency. The theory used is the public policy implementation theory byVan Metter and Van Horn (Agustino, 2006:161-163). This research employed aqualitative approach, with informants selected through purposive samplingtechniques. A total of seven (7) informants participated in the study. Datacollection techniques consisted of observation, interviews, and documentstudies. Based on the research findings, it can be concluded that theimplementation process of the National Health Insurance Program in the BanggaiRegency Health Office has not been fully effective. This is due to one of the sixpolicy implementation indicators not being well executed, namely, the availabilityof resources. The other five indicators—policy standards and objectives,characteristics of the implementing agencies, the disposition of implementers,inter-organizational communication and implementers’ activities, and theeconomic, social, and political environment—show conditions that have beenrunning effectively.